The game production handbook - Chandler, Heather Maxwell, ....- (Burlington, MA : Jones & Bartlett Learning, 2014)
The Game Production Handbook, Third Edition gives producers, leads, and studio managers all the information they need in order to successfully develop a game from concept to release-ready gold master. Fully revised and updated to reflect the rapidly evolving game development landscape, the third edition of this definitive and best-selling text covers pre-production, production, testing, and code release, as well as more specific topics including voiceovers, mo-cap shoots, marketing, localizations, managing external contractors, writing documentation, and project management practices.
Includes bibliographical references (pages 429-435) and index.
Keywords: Computer games -- Programming